2021
DOI: 10.15417/issn.1852-7434.2021.86.3.1068
|View full text |Cite
|
Sign up to set email alerts
|

Retorno al deporte luego de una cirugía de Latarjet: revisión sistemática de la bibliografía

Abstract: Introducción: El objetivo de este estudio fue describir las tasas de retorno al deporte y el nivel alcanzado por los pacientes con inestabilidad de hombro luego del procedimiento abierto y artroscópico de Latarjet. Materiales y Métodos: Seguimos un protocolo prespecificado y registrado en PROSPERO. Evaluamos la calidad de los estudios y utilizamos el sistema GRADE para evaluar la calidad general de la evidencia obtenida en los resultados. Incluimos estudios que evalúan el retorno al deporte de los pacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(81 reference statements)
2
0
0
Order By: Relevance
“…Satisfactory results of return to sports or return to the preinjury level of sports in the Latarjet procedure group in this study may also be due to the stability after Latarjet procedure compared with that after revision Bankart repair surgery. Previous studies, which showed high return to sports rates even in athletes, are consistent with our results [24, 46, 58].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Satisfactory results of return to sports or return to the preinjury level of sports in the Latarjet procedure group in this study may also be due to the stability after Latarjet procedure compared with that after revision Bankart repair surgery. Previous studies, which showed high return to sports rates even in athletes, are consistent with our results [24, 46, 58].…”
Section: Discussionsupporting
confidence: 94%
“…Satisfactory results of return to sports or return to the preinjury level of sports in the Latarjet procedure group in this study may also be due to the stability after Latarjet procedure compared with that after revision Bankart repair surgery. Previous studies, which showed high return to sports rates even in athletes, are consistent with our results [24,46,58]. Despite the good ROWE score and stability, the Latarjet procedure for failed Bankart repair showed signiicantly worse external rotation at side angle (38 degree vs. 60 degree), higher pain VAS score (1.4 vs. 0.8), and more complications after surgery than the revision Bankart repair in the current systematic review and meta-analysis.…”
Section: Discussionsupporting
confidence: 92%